2021
DOI: 10.1080/09712119.2021.1946403
|View full text |Cite
|
Sign up to set email alerts
|

A toxicokinetic study reflecting the absorption, distribution, metabolism and excretion of deoxynivalenol in broiler chickens

Abstract: To identify the specific biomarkers of exposure of DON in chickens, a toxicokinetic study was performed via oral or intravenous application of deoxynivalenol (DON). Doses of 0.75 and 2.25 mg DON/kg of body weight (BW) were administrated intravenously or orally to the chickens. Next, blood samples were collected at several time points and plasma was obtained. Liquid chromatography-tandem massspectrometry (LC-MS/MS) was used to quantify plasma levels of DON and its metabolite DON-3sulphate (DON-3S). A non-compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…There are studies indicating a rapid plasma clearance of DON ( t 1/2 < 1 h) and DON‐3 S; in a recent study, however, no detectable plasma levels of DON and DON‐3 S could be detected in plasma from chickens exposed to DON orally at two different doses (0.75 and 2.25 mg/kg bw) (Riahi et al., 2021a ). In poultry, DON metabolites are excreted via the bile and urines and only little amounts of unmodified DON is found in the excreta.…”
Section: Assessmentmentioning
confidence: 99%
“…There are studies indicating a rapid plasma clearance of DON ( t 1/2 < 1 h) and DON‐3 S; in a recent study, however, no detectable plasma levels of DON and DON‐3 S could be detected in plasma from chickens exposed to DON orally at two different doses (0.75 and 2.25 mg/kg bw) (Riahi et al., 2021a ). In poultry, DON metabolites are excreted via the bile and urines and only little amounts of unmodified DON is found in the excreta.…”
Section: Assessmentmentioning
confidence: 99%
“…Some DON biotransformation routes are identical in various organisms; hence, they produce the same metabolites. Such metabolites include DON-3S, which is produced by both plants and poultry, and DON-3G, the plant metabolite of DON, which has recently been confirmed to be produced by aphids [49][50][51]. Fusarium fungi are capable of DON acetylation, resulting in the formation of 3-acetyl-deoxynivalenol (3-AcDON) or 15-acetyldeoxynivalenol (15-AcDON) [52].…”
Section: Donmentioning
confidence: 99%
“…Similar to DON, this compound undergoes glucuronidation to form deepoxy-deoxynivalenol-15-glucuronide (DOM-15glucuronide) and deepoxy-deoxynivalenol-3-glucuronide (DOM3-glucuronide) [60]. Recent studies carried out on broiler chickens proved that they are able to metabolise DON to DON-3S [49]. It has also been reported that this compound is the main DON metabolite in the eggs of laying hens [50].…”
Section: Donmentioning
confidence: 99%
“…Aflatoxins Highly absorbable (80 to 90%) [74] Induced mild negative effects on the gastrointestinal tract [75] Induced oxidative stress, damaged liver, damaged RNA and DNA, and suppressed immune system [76] Deoxynivalenol Low absorption rate [77] Increased intestinal permeability [ Mycotoxins with high absorption and accumulation rates can remain in edible tissues (meat and liver). Hort et al [93] showed that fumonisins were detected in the liver and fillet muscles.…”
Section: Mycotoxins Absorption Rate In the Gastrointestinal Tract Obs...mentioning
confidence: 99%